Bureaucracy for democracy the dynamics of executive-bureaucracy interaction during governmental transitions [review of] - Thakur, R.N. (1994)
A review of Ledivina V. Carifio, Bureaucracy for Democracy: The Dynamics of Executive-Bureaucracy Interaction During Governmental Transitions (College of Public Administration, University of the Philippines; International Center for Economic Growth; Philippine Institute for Development Studies, 1992 [reprinted 1994]), 198 pages.
Keywords: Book reviews